ECONOMICS AND BIOLOGY – IN SEARCH OF COMMON GROUND - Meyer, Maciej (Acta Scientiarum Polonorum. Oeconomia, 2018)
The article touches on the issues of relations between economics and biology from economic point of view. Its aim is to try to integrate the chosen achievements of both sciences. The author, inspired by statement of Alfred Marshall, supports his position that economics is a branch of biology. Reflections on this topic enhance interdisciplinarity of such fields of study and improve our understanding of the reality. By way of analyzing literature and by using deductive and reductive reasoning relations between economics and biology are pointed out as well as implications. Also, the reasons and indications of the integration are shown as well as existing problems in such approaches.